Energy and Mass Transport of Casson Nanofluid Flow Over a Slanted Permeable Inclined Surface - Rafique, Khuram; IMuhammad Imran, Asjad; Anwar, Muhammad Imran; Misiran, Masnita; Ahmadian, Ali (Springer Netherlands, 2021)
In this problem, examination of Casson nanofluid flow over nonlinear slanted extending sheet with chemical reaction and heat generation/absorption influences are under thought. Nanofluid exhibits in this examination is established on Buongiorno model. The governing nonlinear PDE’s are reduced to nonlinear ODE’s by employing suitable transformations. The Kellerbox numerical technique is considered for simulation of this research. The influence of chemical reaction and nonlinear parameter on concentration and velocity distribution is analyzed. The recovered results exhibit that the impact of inclination and Casson factor reduced liquid velocity. While energy and mass transport rates are increased against inclination factor. Numerical and graphical outcomes are additionally exhibited in tables and graphs